Trans parents and the gendered law: Critical reflections on the Swedish regulation - Alaattinoğlu Daniela; Margaria Alice (Oxford University Press, 2025)
Sweden has attracted international attention for its 2018 legislative provisions which recognize trans parenthood in line with legal gender. This legislation provides that a trans man who gives birth is registered as his child’s father in Sweden, unlike in most countries of the world. This article offers an original engagement with the genesis, peculiarities, and future of the revised Swedish Children and Parents Code, and the criticism it attracts, as an illustrative example of the inherent challenges present in regulating trans parenthood in a gendered, cis- and hetero-normative legal system. The critical analysis of the Swedish provisions investigates two alternative legal models for regulating trans parenthood from a comparative perspective: degendering legal parenthood and misalignment of legal gender and parental status. Looking towards the future, the article normatively embraces a substantive conceptualization of degendering legal parenthood, rather than merely a nominal one, highlighting the need to rethink and redistribute childcare.